International business cycle spillovers - Kamil Yilmaz (TÜSİAD-Koç University Economic Research Forum, 2009)
We apply Diebold-Yilmaz spillover index methodology to monthly industrial production indices to study business cycle interdependence among G-6 industrialized countries since 1958. The business cycle spillover index fluctuates substantially over time, increasing especially after the 1973-75, 1981-82 and 2001 U.S. recessions. The band within which the spillover index fluctuates has widened since the start of the globalization process in the early 1990s. Our most important result, however, concerns the current state of the world economy: In a matter of four months from September to December 2008, the business cycle spillover index recorded the sharpest increase ever, reaching a record level as of December 2008 (See http://data.economicresearchforum.org/erf/bcspill.aspx?lang=en for updates of the spillover plot). Focusing on directional spillover measures, we show that in the current episode the shocks are mostly originating from the United States and spreading to other industrialized countries. We also show that, throughout the period of analysis, the U.S. (1980s and 2000s) and Japan (1970s and 2000s) have been the major transmitters of shocks among the industrialized countries.
Keywords: E32; F41; C32; 330; Business Cycles; Spillovers; Industrial Production; Vector Autoregression; Variance Decomposition; Unit Roots; Cointegration; Konjunkturzusammenhang; Industriestaaten; Kanada; Frankreich; Deutschland; Italien; Japan; Großbritannien; USA